Wendepunkt Klavier? Zu Luigi Nonos Neuorientierung ab ..... sofferte onde serene... - Assis, Paulo de (2024)
Luigi Nono's ...sofferte onde serene... (1976-77) initiates a profound transformation in his compositional strategies, shifting from overt political messages to more nuanced explorations of sound. Focusing solely on one instrument, and recalibrating his compositional techniques, Nono took this piece as an opportunity to reconsider his musical thought and to deeply rethink the act of listening. Scrutinising this transformation from a musical perspective, this essay highlights Nono's renewed engagement with canonical and variation techniques taught by his early mentors Scherchen and Maderna, while also discussing the seamless integration of live and electronic sounds. Taking Nono's redefined musical language as an appeal to rethink listening as a critical process, this paper asserts the political potency of Nono's late style, suggesting that attentive listening is a political act, urging a reconsideration of musical engagement and the ethos of listening in a turbulent world.
FRIS
1
Keywords: Nono, Luigi; Pollini, Maurizio; Metzger, Heinz-Klaus; MetamusicX:Transdisciplinary Encounters in and Beyond Music